Study on Settlement Influence of Newly Excavated Tunnel Undercrossing Large Diameter Pipeline - Qian Xu; Wenchao Zhang; Cheng Chen; Jun Lu; Peng Tang (Advances in Civil Engineering)
With the rapid development of tunnel construction, there will be an increasing number of engineering cases about undercrossing existing pipelines. During the undercrossing process, the settlement control of existing pipelines is relatively strict. If the construction is not handled properly, the existing pipelines will cause a larger settlement, which will affect their normal use. This paper takes an existing pipeline project in Nanjing as the research object and uses numerical simulation to explore the influence of different excavation sequences and grouting reinforcement scopes on the existing pipelines above the newly built tunnels when using shallow tunnel excavation. The results show that the sections are constructed first on both sides of the construction, and the middle section is constructed subsequently, which not only increases the excavation speed but also the pipeline deformation is smaller, especially in controlling the differential settlement on both sides of the pipeline. By studying the relationship between the grouting reinforcement range and the vertical distance from the newly built tunnel to the existing pipeline, it is found that the soil engineering effect within 0.3 d above the arch line is more reasonable, and the feasibility of the proposed scheme is verified through actual monitoring data. This research can provide a reference for similar projects in the future.